2016
DOI: 10.14283/jfa.2016.98
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Frailty May Lead to a State of Burnt Out Type 2 Diabetes

Abstract: Ageing is associated with hyperglycaemic tendency due to the change in body composition leading to accumulation of visceral fat and increased insulin resistance on the one hand and reduced insulin secretion due to decreased number and function of the β-cells of the pancreas on the other. However, with the emergence of frailty there may be a tendency towards normoglycaemia or even hypoglycaemia due to malnutrition, weight loss and reduced physiologic reserve. This shift in glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the AM phenotype, due to malnutrition, frequent episodes of hypoglycaemia are expected [ 19 ] and, deintensification of hypoglycaemic agents is possible [ 21 , 22 ]. The normalisation of HbA1c can occur after the withdrawal of all hypoglycaemic medications, a state called frailty-induced burnt-out diabetes [ 49 ]. The AM frail older people had tight glycaemic control, due to a mismatch between their low body weight and hypoglycaemic drug burden, suggesting the need for deintensification [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the AM phenotype, due to malnutrition, frequent episodes of hypoglycaemia are expected [ 19 ] and, deintensification of hypoglycaemic agents is possible [ 21 , 22 ]. The normalisation of HbA1c can occur after the withdrawal of all hypoglycaemic medications, a state called frailty-induced burnt-out diabetes [ 49 ]. The AM frail older people had tight glycaemic control, due to a mismatch between their low body weight and hypoglycaemic drug burden, suggesting the need for deintensification [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frailty, on the other hand, has also been associated with chronic inflammation and insulin resistance and could therefore affect postprandial thermogenesis [ 118 ]. This hypothesis was examined by Goulet et al; no difference was observed in the DIT between frail women and matched controls, although postprandial insulin resistance was impaired in the frail group.…”
Section: Factors That Affect Ditmentioning
confidence: 99%
“…Weight loss is known to improve insulin sensitivity in internal organs such as the liver and skeletal muscles and reduce fat deposition in the pancreas, which may also improve insulin secretion from the β-cells [ 80 , 81 ]. Therefore, some patients with diabetes in this phenotype have shown spontaneous resolution of hyperglycaemia and normalisation of HbA1c [ 82 ].…”
Section: Impact Of Frailty On Diabetes Trajectorymentioning
confidence: 99%